2020
DOI: 10.1038/s41525-020-00141-0
|View full text |Cite
|
Sign up to set email alerts
|

Associations of the intestinal microbiome with the complement system in neovascular age-related macular degeneration

Abstract: Age-related macular degeneration (AMD) is a leading cause of severe vision loss in the aged population. The etiology of AMD is multifactorial including nutritional factors, genetic variants mainly in the complement pathway, environmental risk factors and alterations in the intestinal microbiome. However, it remains unexplored whether there is an interdependency of these factors leading to the development of AMD. To investigate this issue, a shotgun metagenomics analysis of 57 neovascular AMD and 58 healthy con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
69
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(71 citation statements)
references
References 55 publications
2
69
0
Order By: Relevance
“…17 In Western populations, the associations of ARMS2 and CFH were documented in American, Dutch, Italian, Spanish, and Swiss populations. 14,[18][19][20][21][22][23] In Asian, similar associations were reported in Chinese, Japanese, and Indian populations. 15,[24][25][26][27] However, very limited evidence is available from Asian Malay population, which is also one of the biggest ethnic groups in Asia.…”
Section: Introductionsupporting
confidence: 70%
“…17 In Western populations, the associations of ARMS2 and CFH were documented in American, Dutch, Italian, Spanish, and Swiss populations. 14,[18][19][20][21][22][23] In Asian, similar associations were reported in Chinese, Japanese, and Indian populations. 15,[24][25][26][27] However, very limited evidence is available from Asian Malay population, which is also one of the biggest ethnic groups in Asia.…”
Section: Introductionsupporting
confidence: 70%
“…Furthermore, interdependency of the functional or taxonomic profile of the commensal microbiota and the expression of the complement factor CFH gene or the deregulation of the host complement system may be a potential mechanism that could be linked with AMD [25,26]. Purine signaling pathway genes have been found to be correlated with an unstable immune system response, as seen in autoimmune diseases [27].…”
Section: The Potential Association Between Microbiota and Amdmentioning
confidence: 99%
“…The genes facilitating the aforementioned pathway were found to have augmented expression in patients suffering from AMD compared to controls. Moreover, Zysset-Burri et al [26] examined the association between the intestinal microbiome and the complement system in neovascular AMD and found that single nucleotide polymorphisms in the CFH gene associated with AMD were positively correlated with Negativicutes, a proposed biomarker for AMD. A cause-and-effect relationship remains unclear; however, the intestinal microbiome may potentiate an aberrant complement activation via purine signaling pathways that aid to the development of AMD.…”
Section: The Potential Association Between Microbiota and Amdmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the retina re ects some of the pathological alterations of many neurodegenerative diseases, and may provide information of brain pathology severity 31,32 . In this context, a few recent studies have linked gut microbiome changes with some retinal degenerative diseases 33,34 , including age-related macular degeneration (AMD) [35][36][37][38][39] , glaucoma [40][41][42][43] and diabetic retinopathy 44 , even though the published results vary depending on the type and stage of the disease and between studies. On the other hand, in a previous study we have demonstrated that invasive infection from gastrointestinal microbiome can induce activation of retinal microglia 45 , the primary resident immune cell of the retina.…”
Section: Introductionmentioning
confidence: 99%